Optimizing visual sensor parameters for total coverage maximization - Altahir, A.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
Modeling the sensor coverage is evidently indispensable to meet the requirements of a variety of visual sensor related applications. It is critical to be able to compute the camera coverage and to plan the system accordingly. However, optimizing the visual sensor parameters directly impacts the total performance in visual surveillance applications. This work highlights the theoretical bases of camera modeling. Moreover, the work focuses on calculating the visual sensor coverage via implementing a different set of parameter to maximize the total coverage. A complex scenario is used in the simulation and the results are presented in a comparative manner. The proposed method is capable of computing the camera coverage area in highly occluded scenes. Â© 2014 IEEE.